Developing A Prototype of Module Instruction of Writing Short-Stories Integrated with Samawa Local Wisdom - Ria Saputri; Yeti Mulyati; Sumiyadi; Vismaia S. Damaianti (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
The teaching modules should be carefully designed to not only cover the academic aspects of literature but also to incorporate elements that foster cultural understanding and appreciation. The goal is to create a comprehensive learning framework that allows students to explore literature in a way that is both intellectually stimulating and culturally enlightening. Therefore, this study aims to develop instructional module reflecting the didactic theories and local wisdom principles to facilitate students to practice writing short stories. These theoretical principles are integrated in the module components, namely in the material, training and evaluation sections, student activities in the Module, glossary, and Module illustrations/graphics. The research method uses the R2D2 (Reflective, Recursive, Design and Development) design. Characteristics of the R2D2 model include being recursive, non-linear, sometimes irregular, reflective, and collaborative. However, this model emphasizes learning in a meaningful context. Formative assessment is considered highly important. This research method emphasizes the subjectivity of the model developer. The research commenced with a reflective activity, which is the needs analysis phase, aimed at elucidating the gaps in short story writing instruction. To obtain accurate information regarding the issues at hand, the researcher engaged in a recursive process encompassing all components related to learning and the design of the short story writing module. The results of the research are a prototype of a short story writing module that can be adapted to other text genres in various literary learning materials.